السلوك التمويلي للمؤسسة الاقتصادية الجزائرية بين اقتصاد المديونية واقتصاد الأسواق المالية - دراسة حالة مجمع صيدال- (2020-2022) - العلوي حفيظة; خالفي وهيبة (جامعة الوادي University of Eloued, 2024)
تهدف هذه الدراسة إلى إبراز علاقة النظام المالي السائد بالسلوك التمويلي للمؤسسة، وذلك من خلال تحليل خصوصيات النظام المالي الجزائري وأثرها على السلوك التمويلي لمجمع صيدال كمؤسسة مدرجة ببورصة الجزائر، لاختبار مدى مساهمة هذه الأخيرة في تمويل المؤسسات الاقتصادية في ظل الانتقال من اقتصاد المديونية إلى اقتصاد الأسواق المالية. وقد توصلت الدراسة إلى أن ظهور بورصة الجزائر لا يعد مؤشرا على الانتقال الحقيقي بين النظامين، فالنظام المالي الجزائري لا زال قائما على سيادة التمويل غير المباشر للمؤسسات الاقتصادية، في حين يبقى دور بورصة الجزائر هامشيا ولا يرقى إلى استيعاب حجم الاقتصاد الجزائري، فرغم إدراج مجمع صيدال في بورصة الجزائر منذ أكثر من عشرين سنة، إلا أن ذلك لم يؤثر على سلوكه التمويلي. This study aims to shed light on the relationship between the prevailing financial system and the financing behaviour of the institution by analysing the specificities of the Algerian financial system and its impact on the financing behaviour of the Saidal Group, as an institution listed on the Algerian Stock Exchange, in order to verify the extent of the latter's contribution to the financing of economic institutions in light of the transition from a debt economy to a financial markets economy. The study concludes that the emergence of the Algerian Stock Exchange is not an indicator of the real transition between the two systems, as the Algerian financial system is still based on the dominance of indirect financing of economic establishments, while the role of the Algerian Stock Exchange remains marginal and does not amount to taking over the size of the Algerian economy, Although the SaidalGroup was listed on the Algerian Stock Exchange more than twenty years ago, this did not affect its financing behaviour
The financing behaviour of the Algerian economic institution between the economy of debt and the economy of the financial markets-Saidal Group Case Study - (2020-2022)
Keywords: الهيكل التمويلي; النظام المالي; اقتصاد المديونية; اقتصاد الأسواق المالية; مجمع صيدال; financial structure; financial system; debt economy; financial markets economy; Saidal Group